2022
DOI: 10.20944/preprints202212.0304.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous TOM20 Proximity Labelling: A Swiss-Knife for the Study of Mitochondrial Proteins in Human Cells

Abstract: The majority of mitochondrial proteins are encoded by the nuclear genome and must be imported into the mitochondria. There are two main paths for mitochondrial protein import: post-translational and co-translational import. Co-translational import couples the translation and the translocation of the mitochondrial proteins, alleviating the energy cost typically associated with the post-translational import relying on chaperone systems. The mitochondrial co-translational import mechanisms are still unclear with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…KO of MPV17 in HEK293T cells was performed using CRISPR-Cas9 technology as described previously (Meurant et al, 2023). Briefly, crRNAs targeting the exons 2 (5'-TTTCCACGGGTGAGCGGCCAGGG-3') (Integrated DNA Technologies (IDT), Coralville, USA) or 4 (5'-GGTTTGGATCGGTTCATCCCTGG-3') of the MPV17 gene were designed using CRISPOR bioinformatic resource (Concordet & Haeussler, 2018) and used separately or in combination.…”
Section: Generation Of Ko Cell Linesmentioning
confidence: 99%
See 3 more Smart Citations
“…KO of MPV17 in HEK293T cells was performed using CRISPR-Cas9 technology as described previously (Meurant et al, 2023). Briefly, crRNAs targeting the exons 2 (5'-TTTCCACGGGTGAGCGGCCAGGG-3') (Integrated DNA Technologies (IDT), Coralville, USA) or 4 (5'-GGTTTGGATCGGTTCATCCCTGG-3') of the MPV17 gene were designed using CRISPOR bioinformatic resource (Concordet & Haeussler, 2018) and used separately or in combination.…”
Section: Generation Of Ko Cell Linesmentioning
confidence: 99%
“…Immunoprecipitation was performed as previously described (Meurant et al, 2023). HEK293T cells were scraped in RIPA buffer and the lysate was incubated for 30 min on a rotating wheel at 4 °C before a centrifugation of 10 min at 16.000× g at 4 °C.…”
Section: Immunoprecipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Knockout of SYNJ2B abolished the localization of these mRNAs at the OMM and impaired the cellular stress response by compromising the function of oxidative phosphorylation complexes. Another recent study identified the proteins in proximity to TOM20 (OMM translocase) in human cells and found an overall enrichment of RBPs near TOM20, specifically proteins like AKAP1, LARP4, MED15, and CPSF2, thereby providing a candidate list of RBPs that might be involved in guiding mRNAs to the OMM 25 . Thus, although many RBPs are known to interact with nuclear-encoded mitochondrial transcripts, further studies are required to show that these RBPs play a role in RNA localization.…”
Section: Sequences In 3'utr and Rbp Bindingmentioning
confidence: 99%